Collectivism after modernism the art of social imagination after 1945 - Stimson, Blake; Sholette, Gregory (University of Minnesota Press, 2007)
Organized around case studies spanning the globe from Europe, Japan, and the United States to Africa, Cuba, and Mexico, Collectivism after Modernism covers such renowned collectives as the Guerrilla Girls and the Yes Men, as well as lesser-known groups.
Keywords: Arts, Modern : 20th century : Philosophy; Collectivism : History : 20th century; Art and society : History : 20th century